Impact of the hyperbaric oxygen therapy on the redox status in patients with systemic lupus erythematosus - Rabrenović Milorad; Nikolić Tamara; Rabrenović Violeta; Bradić Jovana; Trešnjić Saša; Petković Anica; Jakovljević Biljana; Mašić Siniša; Bokonjić Dubravko (Vojnosanitetski Pregled)
Background/Aim. Hyperbaric oxygen therapy (HBOT) is a method which increases oxygen solubility in plasma up to 20 times. This effect is very important in the treatment of circulatory disorders, which reduces oxygenation and leads to increased production of inflammatory mediators and free oxygen radicals. The aim of this study was to examine the impact of HBOT on the oxidative stress parameters in the patients with systemic lupus erythematosus (SLE). Methods. This prospective study included 18 females with SLE [American College of Rheumatology (ACR) criteria], average age 52.2 ± 8.82 years, treated with HBOT for 60 min/day, with average partial oxygen pressure of 2.2 atmospheres absolute (ATA), during 10 days, in combination with appropriate medication therapy for SLE. The following parameters were determined in the serum: C-reactive protein (CRP), hemoglobin, creatinine, albumin, complement 3 (C3), antinuclear antibodies (ANA), glomerular filtration rate (GFR) using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formula. In the urine, parameters of oxidative stress were spectrofotometrically determined: levels of superoxide anion radical (O2 •–), hydrogen peroxide (H2O2), nitrites (NO2-) and concentration of thiobarbituric acid reactive substances (TBARS). In hemolysate, the parameters of antioxidant protection: superoxide dismutase (SOD), catalase (CAT) and reduced gluthatione (GSH), were measured. The samples for the analysis were collected three times: before HBOT (initial values), after 10 days of HBOT and 1 month after beginning the treatment in relation to the initial value. Results. We noticed a statistically significant (p < 0.05) decrease in a level of O2 •–, both after 10 days and after 1 month of HBOT (8.26 ± 13.62; 8.39 ± 4.94; 11.92 ± 6.86 nmol/mL, respectively). Values of other parameters of oxidative stress such as NO2-, TBARS and H2O2- showed no significant difference during the monitored period. Regarding the parameters of antioxidant the protection, we revealed slightly higher value of GSH after treatment (initial value: 66.34 ± 16.31; after 10 days of HBOT 79.43 ± 36.77; after 1 month of HBOT69.72 ± 22.32 μmol/mL red blood cells) which was held after a month, but it was not statistically significant. Activity of SOD and CAT, before and after HBOT, did not change significantly. Conclusion. Our results suggested the potential beneficial effects of HBOT on redox status in the patients with SLE by decreasing the levels of O2•–.